A ubiquitous English vocabulary learning system: Evidence of active/passive attitudes vs. usefulness/ease-of-use - Huang, Yueh-Min; Huang, Yong-Ming; Huang, Shu-Hsien; Lin, Yen-Ting (Computers and education, 2012)
English vocabulary learning and ubiquitous learning have separately received considerable attention in recent years. However, research on English vocabulary learning in ubiquitous learning contexts has been less studied. In this study, we develop a ubiquitous English vocabulary learning (UEVL) system to assist students in experiencing a systematic vocabulary learning process in which ubiquitous technology is used to develop the system, and video clips are used as the material. Afterward, the technology acceptance model and partial least squares approach are used to explore students’ perspectives on the UEVL system. The results indicate that (1) both the system characteristics and the material characteristics of the UEVL system positively and significantly influence the perspectives of all students on the system; (2) the active students are interested in perceived usefulness; (3) the passive students are interested in perceived ease of use. ► We develop a ubiquitous English vocabulary learning system. ► Ubiquitous technology and video clip are used to develop the system. ► Technology acceptance model is used to explore the perspectives of students. ► Active students are interested in perceived usefulness. ► Passive students are interested in perceived ease of use.